2023
DOI: 10.3390/ijerph20043287
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Low-Cost Uroflowmetry for Patient Telemonitoring

Abstract: Uroflowmetry (UF) is a crucial guideline-recommended tool for men with benign prostatic obstruction (BPO). Moreover, UF is a helpful decision-making tool for the management of patients with lower urinary tract symptoms (LUTS) and benign prostatic hyperplasia (BPH). In the last few years, telemedicine and telehealth have increased exponentially as cost-effective treatment options for both patients and physicians. Telemedicine and telehealth have been well positioned during the COVID-19 pandemic to prevent healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…To overcome these limitations, numerous studies have been conducted to identify new biomarkers, and several miRNAs have been shown to be involved in the development and progression of PCa [ 65 , 66 , 67 ]. In the selected studies, we found that umiRNAs could be used as valuable tools in differentiating PCa from benign rising of PSA.…”
Section: Resultsmentioning
confidence: 99%
“…To overcome these limitations, numerous studies have been conducted to identify new biomarkers, and several miRNAs have been shown to be involved in the development and progression of PCa [ 65 , 66 , 67 ]. In the selected studies, we found that umiRNAs could be used as valuable tools in differentiating PCa from benign rising of PSA.…”
Section: Resultsmentioning
confidence: 99%
“…In clinical diagnostics, uroflowmetry is a guidelinerecommended pivotal tool for evaluating BPH obstructive symptoms, with the severity of these symptoms dictating the need for surgical intervention (56). With the advancement of portable home devices, the acquisition of UF data has become increasingly accessible and cost-effective (57). Comprehensive UF information aids in the precise assessment of LUTS symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of obstructive symptoms can be initially determined through the assessment of prostate volume and the International Prostate Symptom Score (IPSS) ( Foo, 2019 ). In addition, uroflowmetry is also a crucial diagnostic indicator in assessing BPH ( Pandolfo et al, 2023 ). The etiology of BPH is multifactorial, with aging and hormonal imbalances being widely acknowledged as primary contributors ( Devlin et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%